Thematic Structuring of the General Mathematics Curriculum at the Secondary Level Utilizing Grounded Theory - Tousif, Madiha; Bahoo, Rabia; Akram, Muzammila (Pakistan Journal of Humanities and Social Sciences, 2024)
The objectives of the current study were to examine the shortcomings of the existing secondary-level General Mathematics curriculum, identify contemporary trends in the subject, and suggest a thematic division for the sector-wise organization of the curriculum. Grounded Theory was used as the research design for this study. The study used Creswell’s systematic approach, utilizing structured data analysis processes like open coding, axial coding, and selective coding, and creating a sectorial division. According to Creswell, this investigation was divided into three stages. At the first stage, prominent teachers of General Mathematics participated in semi-structured interviews using an interview protocol as a research instrument. At the second stage, the potential causes of the curriculum's shortcomings were determined. At the third stage, contemporary trends in mathematics were discovered through the use of document analysis to examine the mathematics curricula of developed nations. Ultimately, the data gathered during the three processes described above was used to create a thematic division. Purposive sampling was used to gather data from a sample of 22 teachers. Conclusion of stage I showed that curriculum of General Mathematics has imperfectness that prevent it from meeting the cognitive and creative requirements. Conclusion of stage II explained the causes of these deficiencies. Conclusion of stage III confirmed that in order to prepare students for the modern world, contemporary tendencies should be inferred. Consequently, a supposed outline of curriculum of Mathematics was designed.